Exergy analysis of solar desalination systems based on passive multi-effect membrane distillation. (November 2020) - Signorato, Francesco; Morciano, Matteo; Bergamasco, Luca; Fasano, Matteo; Asinari, Pietro
Abstract: Improving the efficiency and sustainability of water treatment technologies is crucial to reduce energy consumption and environmental pollution. Solar-driven devices have the potential to supply off-grid areas with freshwater through a sustainable approach. Passive desalination driven by solar thermal energy has the additional advantage to require only inexpensive materials and easily maintainable components. The bottleneck to the widespread diffusion of such solar passive desalination technologies is their lower productivity with respect to active ones. A completely passive, multi-effect membrane distillation device with an efficient use of solar energy and thus a remarkable enhancement in distillate productivity has been recently proposed. The improved performance of this distillation device comes from the efficient exploitation of low-temperature thermal energy to drive multiple distillation processes. In this work, we analyze the proposed distillation technology by a more in-depth thermodynamic detail, considering a Second Law analysis. We then report a detailed exergy analysis, which allows to get insights on the production of irreversibilities in each component of the assembly. These calculations provide guidelines for the possible optimization of the device, since simple changes in the original configuration may easily yield up to a 46% increase in the Second Law efficiency.